SINTESIS ZEOLIT DARI LIMBAH AMPAS TEBU VARIASI WAKTU KRISTALISASI DAN RASIO Si/Al - Riang, Alfonsa Juwita, S.Si, M.Si., Sriatun, M.Si., Dra. Taslimah (Chem Info Journal, 2013)
Zeolite synthesis from bagasse was done in this research. Bagasse camouflage at 550oC for 4 hours, Silica in bagasse ash was extracted by dissolving in NaOH and heated. Sodium silicate mix with sodium aluminate then placed on a Teflon container and heated in an oven for the crystallization process. The study begins with the crystallization time 1,3,5,7 days with Si/Al ratio 50 and continued with the Si/Al ratio 75, and 100 by using the best of the crystallization time.The heating time of 1 and 3 days produced amorphous while the 5 and 7 days of heating time have resulted Zeolite with the best crystallinity of the zeolite in the 7 days of heating. Increasing of Si/Al ratio showed a decrease in crystallinity. Crystallinity of the zeolite with the best results obtained at the time of crystallization of 7 days with a ratio Si/Al 50. The resulting zeolite is Hydrogen Aluminum Silicate (H4Al2Si2O9), and there are mixture of the Sodium Silicate Hydrate (Na2SiO3.9H2O), Sodium Hydrogen Silicate Hydrate (Na2(H2SiO4).7H2O) with consecutive crystal size 340.29 nm; 362.84 nm; 392.21 nm and the comparison of the composition is 39.6%, 39.2%, 21.16%